TINJAUAN FATWA DSN MUI TERHADAP PRODUK PEMBIAYAAN MULTIJASA DI KOPERASI SYARIAH - Sugiarto, Suprihantosa; Ivana Cahyaningtias (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2024)
Abstract: This article aims to analyze further the implementation of the multiservice ijarah (financing) contract in Islamic cooperatives in terms of the DSN-MUI fatwa. Multijasa Ijarah financing is the most popular product because it is considered the most suitable for the various needs of cooperative members, especially at the Kediri Insan Sejahtera Sharia Employee Cooperative (KKS). In this research, multijasa ijarah financing at Sharia Employee Cooperative (KKS) Insan Sejahtera Kediri will be reviewed from two DSN MUI fatwas, namely DSN-MUI fatwa NO: 09/DSN-MUI/IV/2000 and DSN-MUI fatwa NO: 44/DSN-MUI/VIII/2004, by using the qualitative method with the type of field research and using a descriptive analytical approach. The results of this study are: 1) Multijasa ijarah financing is only devoted to permanent employees of KKS Insan Sejahtera Kediri and can be used for takeover services financing, which can be used to meet the consumptive needs of members, including the cost of paying debts or loan repayments, employee teacher children's education costs, medical expenses, home renovation costs, and others. 2) The implementation of the multijasa ijarah contract at KKS Insan Sejahtera Kediri in terms of the DSN MUI Fatwa NO: 09/DSN-MUI/IV/2000 is not fully following the fatwa. 3) Implementation of multijasa ijarah contract at KKS Insan Sejahtera Kediri in terms of Fatwa DSN MUI NO: 44 DSN-MUI/VIII/2004 has been in accordance based on the fatwa. It is explained in the fatwa that multijasa financing is legal jaiz by using ijarah or kafalah contracts. Abstrak: Artikel ini bertujuan untuk menganilis lebih mendalam tentang implementasi akad ijarah (pembiayaan) multijasa pada koperasi syariah ditinjau dari fatwa DSN-MUI. Pembiayaan Ijarah Multijasa menjadi produk yang paling banyak diminati karena dianggap paling cocok dengan berbagai kebutuhan anggota koperasi terutama pada Koperasi Karyawan Syariah (KKS) Insan Sejahtera Kediri. Dalam penelitian ini pembiayaan ijarah multijasa pada Koperasi Karyawan Syariah (KKS) Insan Sejahtera Kediri akan ditinjau dari dua fatwa DSN MUI yaitu fatwa DSN-MUI NO: 09/DSN-MUI/IV/2000 dan fatwa DSN-MUI NO: 44/DSN-MUI/VIII/2004 dengan menggunakan metode kualitatif, dengan jenis penelitian lapangan serta menggunakan pendekatan deskriptif analitis. Hasil dari penelitian ini yaitu 1) Pembiayaan ijarah multijasa hanya dikhususkan pada pegawai tetap KKS Insan Sejahtera Kediri saja dan bisa digunakan untuk Pembiayaan Jasa Takeover yang dapat digunakan untuk memenuhi kebutuhan konsumtif anggota meliputi biaya membayar hutang atau pelunasan pinjaman, biaya pendidikan anak guru karyawan, biaya berobat, biaya renovasi rumah, dan lainnya. 2) Implementasi akad ijarah multijasa pada KKS Insan Sejahtera Kediri ditinjau dari Fatwa DSN MUI NO: 09/DSN-MUI/IV/2000 belum sepenuhnya sesuai dengan fatwa. 3) Implementasi akad ijarah multijasa di KKS Insan Sejahtera Kediri ditinjau dari Fatwa DSN MUI NO: 44 DSN-MUI/VIII/2004 telah sesuai berdasarkan fatwa tersebut. Dijelaskan dalam fatwa bahwa pembiayaan multijasa hukumnya jaiz dengan menggunakan akad ijarah atau kafalah.